COLLOCATIONS AND THEIR IMPORTANCE IN LANGUAGE STUDY - Sevara Saidqulova,; Gulkhayo Shukurova,; Hakima Abdullajonova, (TADQIQOTLAR, 2025)
Abstract Collocations — habitual and predictable word combinations — represent one of the most crucial yet often underappreciated aspects of linguistic competence. Mastery of a language extends beyond grammatical accuracy and vocabulary size; it involves the intuitive understanding of how words naturally co-occur within authentic contexts. This  paper  examines  the  theoretical  underpinnings  of  collocations,  their  linguistic classifications,  and  their  indispensable  role  in  language  acquisition,  fluency,  and pedagogical  application.  Drawing  upon  insights  from  corpus  linguistics,  cognitive linguistics, and applied language studies, the paper argues that collocational awareness bridges the gap between formal linguistic knowledge and communicative competence. It discusses how collocations contribute to the naturalness, idiomaticity, and efficiency of communication, and how their neglect in language pedagogy leads to fossilized errors and non-native-like production. Emphasis is placed on integrating collocation learning  into  vocabulary  instruction  and  communicative  teaching  frameworks.  The paper  concludes  that  collocational  competence  should  be  prioritized  as  a  central component of language study and curriculum design to produce learners who not only know a language but can also live it fluently.